Akhlak Tasawuf sebagai Kajian Keilmuan - Edi Kurniawan Farid (Asy-Syari’ah : Jurnal Hukum Islam, 2017)
The main purpose of this article is to explore akhlaq and tasawuf as a sience which is learned at all of islamic university in Indonesia. It is grouped as basic competence subject that is obliged by the Islamic University for all students to take this subject. The article tries to discuss this subject by explaining the meaning and definition of each akhlaq and tasawuf according to ulama’, correlation between them, and the urgency of akhlaq tasawuf in Islam. The article shows that akhlaq tasawuf is an important study among another Islamic studies, because of it’s object which is has strong correlation and implicable with the one’s soul and spiritual. Finally, studying akhlaq tasawuf want to build the understanding that worshiping god is not only building good relation to god, but also to all his creators.